PENGARUH KONSENTRASI Na-CMC (Natrium-Carboxymethyl Cellulose) TERHADAP KARAKTERISTIK COOKIES TEPUNG PISANG KEPOK PUTIH (Musa paradisiaca L.) PREGELATINISASI - Valentine Valentine; Anita Maya Sutedja; Yustinus Marsono (Faculty of Agricultural Technology, University of Jember, 2015)
Musa paradisiaca L. processed into banana flour can increase the diversification of banana utilization and improve its economical value. One of the diversified product of banana flour is cookies. Utilization of banana flour as the raw material can cause a sense of starchy cookies on the product, so it has to do pregelatinized. Pregelatinized of banana flour do with a steam treatment and maintain the steam temperature at 73oC±3 for 20 minutes. Replacement of wheat flour with pregelatinized banana flour will reduce gluten, to produce cookies with texture is very friable and sandy mouthfeel. In this study examined the addition of hydrocolloid Na-CMC (Natrium-Carboxymethyl Cellulose) to replace the role of gluten. The aim of this study was to determine the effect of concentrations of Na-CMC and determine the concentration of Na-CMC which produces of cookies with white kepok banana (Musa paradisiaca L.) pregelatinized flour acceptable to panels. Concentrations treatment of Na-CMC resulted in significant effects (α=5%) due to an increase of concentration 0,00-1,50% on the physicochemical characteristics (moisture content, specific volume, power broken and color) and sensoric properties (color, taste, aroma, broken power and mouthfeel). Cookies Musa paradisiaca L. Pregelatinized Flour with concentrations of Na-CMC 1.50% give the best characteristic, with the water content of 2.66%; specific volume of 3.87 ml/g; hardness of 2855.06 g/cm; lightness 62.93; redness 7.05; yellowness 19.73; chroma 21.08; hue 73.33; and sensoric score for color, taste, aroma, hardness and mouthfeel with each score 5.93; 5.87; 6.00; 6.19 and 5.97, out of score level 1 to 7 respectively.Keywords: cookies, white kepok banana pregelatinized flour, Na-CMC